Reanalyzing Jupiter ISO/SWS data through a more recent atmospheric model - Ribeiro, J; Machado, P; Perez-Hoyos, S; Dias, JA; Irwin, P (MDPI, 2023)
The study of isotopic ratios in planetary atmospheres gives an insight into the formation history and evolution of these objects. The more we can constrain these ratios, the better we can understand the history and future of our solar system. To help in this endeavour, we used Infrared Space Observatory Short Wavelength Spectrometer (ISO/SWS) Jupiter observations in the 793–1500 cm (Formula presented.) region together with the Nonlinear Optimal Estimator for MultivariatE Spectral analySIS (NEMESIS) radiative transfer suite to retrieve the temperature–pressure profile and the chemical abundances for various chemical species. We also used the 1500–2499 cm (Formula presented.) region to determine the cloud and aerosol structure of the upper troposphere. We obtained a best-fit simulated spectrum with (Formula presented.) for the 793–1500 cm (Formula presented.) region and (Formula presented.) for the 1500–2499 cm (Formula presented.) region. From the retrieved methane abundances, we obtained, within a 1 (Formula presented.) uncertainty, a (Formula presented.) C/ (Formula presented.) C ratio of 84 ± 27 and a D/H ratio of (3.5 ± 0.6) × 10 (Formula presented.), and these ratios are consistent with other published results from the literature.